The overall fatty acid absorption controlled by basolateral chylomicron excretion under regulation of p-JNK1 - Stremmel, Wolfgang; Staffer, Simone; Wannhoff, Andreas; Pathil-Warth, Anita (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2017)
Suppression of fatty acid absorption is one goal to fight obesity. However, the responsible molecular mechanism is poorly understood. Aim of the present study was the search for the key regulator of the overall fatty acid absorption mechanism and its pharmaceutical modulation. As experimental tool we employed the polarized human intestinal tumor derived cell line CaCo2. Here we showed that influx of fatty acids is mediated by an apical heterotetrameric plasma membrane protein complex of which the calcium-independent membrane phospholipase A2 (iPLA2ß) is one constituent. The newly synthesized bile acid-phospholipid conjugate ursodeoxycholate-lysophosphatidylethanolamide (UDCA-LPE) blocked iPLA2ß, which structurally disrupted the fatty acid-uptake complex. Furthermore, the inhibition of iPLA2ß lead to reduction of cytosolic lysophosphatidylcholine (LPC) production which suppressed p-JNK1, as a central regulator of metabolism. In a concerted action low p-JNK1 levels prohibited synthesis of the members of the fatty acid uptake complex as well as of apolipoprotein B and the connected members of the basolateral vesicular chylomicron excretion machinery, thereby inhibiting cellular lipid excretion. The basolateral chylomicron release was shown to determine the overall fatty acid-absorption capacity as rate limiting step, whereas apical uptake replenishes the cellular stores, enabling continuous transcellular movement of fatty acids. In conclusion, the UDCA-LPE mediated inhibition of p-JNK1 represents a powerful tool to control intestinal absorption of fatty acids and, thus may be employed as a drug to treat obesity.
Gesehen am 25.08.2020